Of Marbles and Minecraft: Designing STEM Educational Games for Culturally Diverse Young Learners in Malaysia - Chuah, Kee Man; Fitri Suraya, Mohamad; Jacey Lynn, Minoi; Muhammad Kamarul, Kabilan (2021)
Gamification has been widely touted as a useful approach in motivating learners to learn subjects that are perceived as challenging, such as science, technology, engineering, and mathematics (STEM). This paper reports the process of considering various cultural and social factors in the design of educational games using game design thinking approach. Educational games for STEM subjects were designed and developed through an iteration process that considered the contextual significance of learners’ diverse cultural backgrounds. Online and traditional games were used as sources of inspiration, and they were re-designed to fit with learner’s interests and context. The findings from 42 learners who played the role as the game designers showed significant impact of the empathy stage in the design loop where cultural elements were shared and integrated into the design. The participatory design approach proves to be very useful in encouraging learners to provide their ideas. Some learners who had limited exposure to computer or video games were still able to combine suitable game mechanics and draw ideas from their surroundings to create their own games. The findings also reveal differing viewpoints of urban and rural learners with regards to use of games of learning. The outcomes from this study provided valuable insights in the formulation of a framework for game design that takes into account learners' diversity.